Multi-center Study for Interprofessional Education in Community Settings to Develop Online Peer Assessment System - Doni Widyandana; Fitriana; Eti Poncorini Pamungkasari; Fatikhu Yatuni Asmara; Tri Nur Kristina (Proceeding of International Conference on Science, Health, And Technology, 2019)
Interprofessional Education (IPE) is becoming a worldwide trend to be applied to the education of health workers. IPE is believed to be able to prepare students to be more ready to collaborate with various health professions in the world of work later. However, the challenge of implementing an ideal education and assessment system is still being debated. Evaluate the education system and IPE assessment of multicenter (3 universities) in achieving 4 domains of IPE competency. Furthermore, the results are used as a base for recommendations to improve the education system and student assessment. Cross sectional study to evaluate education process and IPE assessment take part into three health institute centers. The institutions are a part of JOGLOSEMAR (Jogjakarta, Solo and Semarang City). Research intended to evaluate competence achievement on 4 IPE domains following IPEC 2016. A multicenter survey involved students (n= 500), focused group discussion with academic lecturer (n=10 and focused group discussion with student representatives (n=10) established to evaluate the education system and IPE assessment. A qualitative descriptive data analysis performed by 2 independent researchers. Multicenter survey indicate that students have receiving positive impact from the IPE program to achieve 4 designated competence. FGD shows that challenge for the program occurred from activity scheduling as it necessary to accommodate the whole professions participation. Besides, challenge also coming from the ability of academic lecturer to provide sufficient supervision, availability of learning resources e.g. guide book and assignments, transparent and reliable evaluation items and last distinct guideline of student activity and any kind of violation. IPE Program from 3 academic center shows similar result, indicating that the program provides positive result to achieve student competencies. Challenges among the students and academic lecturer require appropriate management in order to organize a responsible study activity.